Appendectomy and appendicitis do not increase colorectal cancer risk: evidence from Mendelian randomization - Wei, Wei; Wang, Juanhong; Yu, Daihua; Liu, Wei; Zong, Lei (Frontiers in Oncology, 2024)
Background Acute appendicitis (AA) is one of the most prevalent acute abdominal diseases and appendectomy is the definitive treatment of appendicitis. However, whether appendicitis and appendectomy cause colorectal cancer (CRC) is controversial. The results of observational studies are contradictory, but randomized controlled trials (RCT) cannot be conducted . Methods Data of appendectomy, AA, and CRC were obtained from the IEU Open GWAS project. We selected several Genome-wide association studies (GWAS) summary statistics for CRC: statistics for colon cancer (CC) were obtained from MRC-IEU and Neale lab, respectively; statistics for rectum cancer (RC) were obtained from MRC-IEU and FinnGen, respectively; statistics for CRC were provided by Sakaue S et al. Mendelian randomization (MR) was used to evaluate the causal relationships between exposure and outcomes. Inverse variance weighting (IVW) was the most important analysis method. Meta-analysis was used to summarize the results of IVW to increase the reliability and sensitivity analysis was used to evaluate the robustness of the results. Results According to the results of IVW, appendectomy did not increase risk of CC: MRC-IEU (OR:1.009, 95%CI:0.984-1.035, P=0.494), Neale lab (OR:1.016, 95%CI:0.993-1.040, P=0.174); Appendectomy also did not increase risk of RC: MRC-IEU(OR:0.994, 95%CI:0.974-1.014, P=0.538), FinnGen(OR:2.791, 95%CI:0.013-580.763, P=0.706); Appendectomy also did not increase risk of CRC: Sakaue S(OR:1.382, 95%CI:0.301-6.352, P=0.678). Appendicitis did not increase risk of CC: MRC-IEU(OR:1.000, 95%CI:0.999-1.001, P=0.641), Neale lab(OR:1.000, 95%CI:1.000-1.001, P=0.319); Appendicitis also did not increase risk of RC: MRC-IEU(OR:1.000, 95%CI:0.999-1.000, P=0.361), FinnGen(OR:0.903, 95%CI:0.737-1.105, P=0.321); Appendicitis also did not increase risk of CRC: Sakaue S (OR:1.018, 95%CI:0.950-1.091, P=0.609). The results of Meta-analysis also showed appendectomy (P=0.459) and appendicitis (P=0.999) did not increase the risk of CRC. Conclusions Appendectomy and appendicitis do not increase the risk of colorectal cancer. More clinical trials are needed in the future to verify the causal relationships.